Design of an Athermal Interferometer Based on Tailored Subwavelength Metamaterials for On-Chip Microspectrometry - Umair A. Korai; Alaine H. Bermello; Michael J. Strain; Ivan Glesk; Aitor V. Velasco (IEEE Photonics Journal, 2019)
Temperature dependence is one of the main challenges of the silicon-on-insulator platform due to the large thermo-optic coefficient of its core material. In this work we propose a design of an all-passive athermal silicon-on-insulator Mach-Zehnder interferometer (MZI) based on the standard silicon material platform. The MZI's temperature compensation is achieved by optimizing the relative length of the wire and subwavelength grating arms and by tailoring the thermal response of the subwavelength structure. Simulations of the device performance showed that an overall temperature sensitivity of 7.5 pm/K could be achieved over a 100 nm spectral range near the 1550 nm region.